The Non-denuded Mucoperiosteal Palatoplasty Technique in Precipitating Healing Process of Palatal Lateral Defect - Irwansyah, Denny; Bangun, Kristaninta; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Conventional two-flap palatoplasty technique which is a very common technique used including in our center, will result in lateral defects without any periosteal coverage. In this conventional technique, epithelialization of lateral defect was achieved within 3-4 weeks. These denuded lateral defects are prone to contamination and infection. The wound healing process in these wound will involve wound contraction, trigger scar formation, and will result in maxillary growth impairment. In our center, the retrospective study showed that conventional two-flap palatoplasty technique resulted in a fair maxillary growth (mean Goslon score=3.5). Thus, we explore other technique, which is non-denuded mucoperiosteal palatoplasty technique. We intend not to elevate all layers of mucoperiosteal flap in order to gain lateral defect covered by a thin sub-mucosa and periosteal layer. We assume that this technique will precipitate the re-epithelialization process. Faster re-epithelialization is expected to decrease wound contraction thus reducing scar formation, and in the long run will result in good maxillary growth. Method: Total 48 patients with unilateral or bilateral cleft palate were divided into 2 groups. Twenty-four patients underwent the non-denuded mucoperiosteal technique (intervention group) and another 24 patients underwent the conventional two-flap palatoplasty technique (control group). Evaluation of lateral defect closure was done in both groups and compared statistically. Result: Faster epithelialization was significantly influenced by age, WBC count and non-denuded mucoperiosteal technique.Summary: The non-denuded mucoperiosteal technique, along with age and WBC count, significantly accelerate the process of epithelialization of lateral defect post palate repair.